Handbook of research on resource management for pollution and waste treatment - Affam, Augustine Chioma, 1979-; Ezechi, Ezerie Henry, 1983- (IGI Global, Engineering Science Reference (an imprint of IGI Global), 2020)
"This book examines resource management strategies for waste and pollution treatment methods"-- Provided by publisher.
Keywords: Pollution.; Pollution prevention.; Environmental monitoring.; Refuse and refuse disposal.; Sewage -- Purification.; elektronické knihy; electronic books